2021
DOI: 10.1177/0973258621992644
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Creative Communications and Gamification in Student Engagement in Higher Education: A Sentiment Analysis Approach

Abstract: This article aims to explore gamification tools in services and higher education environments and their role in creating student engagement. The research adopts a qualitative method based on quasi-experimental design. Participants from a higher education institution are exposed to gamification activities during a full semester. Researchers use the sentiment analysis (SA) technique based on a text-mining approach to analyse the data. Findings reveal that participants perceive gamification in service settings as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 83 publications
0
12
0
1
Order By: Relevance
“…As noted above, gamified learning and game-based learning (GBL) tend to exert positive effects on learning outcomes and the learners themselves. For example, it has been pointed out that the development of basic personal skills, including highly valuable soft skills for organizations such as those related to teamwork, as well as learning in a variety of subjects, can be effectively supported by games in an efficient, attractive and motivating way [30,[37][38][39][40]. However, the use of games for learning purposes in HIEs is not without controversy, not only in terms of whether and to what extent their effects are always beneficial [41] but also with respect to their theoretical foundation [30,42].…”
Section: Does Game-based Learning Work In Hies? Its Theoretical Foundationmentioning
confidence: 99%
“…As noted above, gamified learning and game-based learning (GBL) tend to exert positive effects on learning outcomes and the learners themselves. For example, it has been pointed out that the development of basic personal skills, including highly valuable soft skills for organizations such as those related to teamwork, as well as learning in a variety of subjects, can be effectively supported by games in an efficient, attractive and motivating way [30,[37][38][39][40]. However, the use of games for learning purposes in HIEs is not without controversy, not only in terms of whether and to what extent their effects are always beneficial [41] but also with respect to their theoretical foundation [30,42].…”
Section: Does Game-based Learning Work In Hies? Its Theoretical Foundationmentioning
confidence: 99%
“…Among these studies, an increasing trend of using third-parties SA software emerges. MeaningCloud (Bilro et al, 2022) or RStudio packages (Okoye et al, 2020) facilitate the utilization of SA in broader educational contexts and better explore its potential contributions in this field. However, we caution against the massive adoption of these solutions, as they might not be successfully enough in achieving current challenges of SA (e.g., use of specialized vocabulary, interpretation of negations and idioms, conducting SA at topic level within a text… in highly formal contexts), causing significant methodological flaws in research results.…”
Section: Information Extractionmentioning
confidence: 99%
“…In this kind of role-playing game, groups of students, with different backgrounds in their respective field of study, were given roles in forms of cards and would converse with each other about a given scenario [4]. In addition, it has been suggested that the implementation of gamified aspects in the teaching process has been successful in the field of student engagement, which might refer to gamified quizzes and not a full game [5]. There is also application regarding stakeholder engagement in communities, as video game RPGs have shown promising results.…”
Section: Literature Reviewmentioning
confidence: 99%